MOTIVASI, SIKAP DAN PERSEPSI TERHADAP PERILAKU KONSUMEN DALAM MENGGUNAKAN SMARTPHONE MERK SAMSUNG PADA MASYARAKAT KOTO BARU HIANG KAB. KERINCI - Indra Budaya; Dona Elvia Desi; Zela Sri Mayola (Gapenas Publisher, 2022)
This problem is motivated by the use of Samsung brand smartphones. The research objectives are: 1) To determine the partial effect of motivation, attitudes and perceptions on consumer behavior in using Samsung brand smartphones in the Koto Baru Hiang Kab community. kerinci, 2) To determine the effect of motivation, attitudes and perceptions partially on consumer behavior in using Samsung brand smartphones in the Koto Baru Hiang Regency community. kerinci. The population in this study is the people of Koto Baru Hiang Kab. Kerinci. The sample for this study amounted to 90 respondents with the sampling technique of accidental sampling. The data analysis tools used are Likert Scale, Multiple Linear Regression Analysis, Partial and Simultaneous Coefficient of Determination, t-test and f-test. Based on the results of the study indicate that: Motivation has a significant and positive effect on consumer behavior 0.000 <0.05. Attitudes have a significant and positive effect on consumer behavior 0.000 <0.05. Perception has a significant and positive effect on consumer behavior 0.000 <0.05